On the use of evanescent electromagnetic waves in the detection and identification of objects buried in lossy soil. - Smith, G.S (IEEE Transactions on antennas and propagation)
In some electromagnetic (EM) systems proposed for the detection of buried objects, such as landmines, the transducers (antennas) are located very close to the surface of the Earth. The coupling of energy into the Earth is then by the near field of the transducers, or, more precisely, by evanescent waves as well as propagating waves in the spectrum for the radiation from the transducers. Evanescent waves also contribute to the coupling of the scattered field from the shallowly buried object to the transducers. In this paper, we use simple models based on a plane-wave spectral analysis to perform a preliminary examination of the role that evanescent waves can play in the detection and identification of the buried object. The degree to which features in the image of the object can be resolved is of particular interest, since the features can be used to distinguish the object from clutter (such as rocks). The effect of loss in the soil on imaging is also of interest